Ners Interest Factors in Independent Practice (Qualitatif Research) - Harlina Putri Rusiana; Dewi Nur Sukma Purqoti; Rias Pratiwi Safitri; Fitri Romadonika; Baiq Nurul Hidayati; Ilham; Ema Safitri (Journal for Quality in Public Health, 2022)
The issuance of the The issuance of the Undang-undang Keperawatan No. 38 of 2014 which was strengthened by Peraturan Menteri Kesehatan No. 26 of 2019 has provided legal certainty that nurses are allowed to establish independent nursing practice places, both individually and in groups. Although regulations on independent nursing practice have long been developing, and there are more than 3147 nurses in Mataram City, in Mataram City there is only one independent nursing practice. This study was to describe the factors that influence nurses' interest in carrying out independent nursing practice in the working area of DPD PPNI Mataram City in 2021. The research used was descriptive qualitative research and the selection of informants in this study used purposive sampling, technical The data collection used was by conducting indepth interviews, observation and documentation, while the informants in this study were key informants and source informants. Indicates that the main factors that influence nurses' interest in implementing independent nursing practice are the lack of understanding of the regulations governing independent nursing practice, financial sources, motivational factors and the last factor of work environment.